Record production and the construction of authenticity in the Beach Boys and late-sixties American rock - Butler, Jan (2010)
This thesis explores the paradox that occurred at the time that rock emerged as a new genre in America in the mid-1960s. Recordings were becoming increasingly manipulated in the studio, but at the same time there emerged a growing ideology of authenticity that developed as the decade progressed, first focussing on records, but ending by privileging live performance. The study falls into three parts. The first traces the development of authenticity in relation to music through history and explores its possible nature in order to illuminate the development of authenticity in relation to rock in the 1960s. The second section writes a history of the record industry in the 1960s, focussing on organisational practices, which I argue were strongly influenced by an ideology of authenticity related to beliefs about the conditions necessary to create art in a commercial framework. These organisational changes lead to the adoption by the industry of the figure of the entrepreneur producer. The final section looks at how the industry interacted with the conflicting ideologies of authenticity that were developed in the counterculture in relation to rock, employing rock cultural intermediaries both to bring rock bands into the industry, and to sell their music back to the counterculture from which they came. The more theoretical points of my discussion are exemplified through the use of a case study of the Beach Boys, whose career spans the decade, and who, despite early success as a rock band, experienced difficulty negotiating the changing ideologies of authenticity that emerged as the decade progressed.